Articulatory variability of clutterers - Hartinger, Mariam; Mooshammer, Christine (ZAS Papers in Linguistics, 2005)
In order to investigate the articulatory processes of the hasty and mumbled speech of clutterers, the kinematic variability was analysed by means of electromagnetic midsagittal articulography (EMMA). In contrast to stutterers, clutterers improve their intelligibility by concentrating on their speech task. Variability is an important criterion in comparable studies of stuttering and is discussed in terms of the stability of the speech motor system. The aim of the current study was to analyse the spatial and temporal variability in the speech of three clutterers and three control speakers. All speakers were native speakers of German. The speech material consisted of repetitive CV-syllables and foreign words, because clutterers have the most severe problems with long words which have a complex syllable structure. The results showed a higher quotient of variation for clutterers in the foreign word production. For the syllable repetition task, no significant differences between clutterers and controls were found. The extremely large and variable displacements were interpreted as a strategy that helps clutterers to improve the intelligibility of their speech.